PENGARUH KOMPENSASI FINANSIAL DAN KOMPENSASI NON FINANSIAL TERHADAP KEPUASAN KERJA KARYAWAN PADA SWEET GARDEN GUEST HOUSE MALANG - Ellyn Eka Wahyu (Politeknik Negeri Malang, 2017)
This study aims to determine the financial compensation affect partially on employee job satisfaction, to know non-financial compensation partially effect on employee job satisfaction and to know financial compensation and non-financial compensation simultaneously influence on job satisfaction at Garden Guest House Malang. The type of research conducted in this study is the type of explanatory research (Explanatory Research). The result of data analysis which have been done in this research is on the result of t test analysis (partially) financial compensation variable (X1) have a partial and significant effect to employee work satisfaction (Y). The results of the test calculation for the non-financial compensation variable (X2), show that non-financial compensation partially and significantly affect the employee job satisfaction (Y). The simultaneous test results (F) performed show that both financial compensation and non-financial compensation variables simultaneously (together) significantly influence employee job satisfaction. Job satisfaction can arise because employee welfare rights have been fulfilled is financial compensation and non-financial compensation.